2007
DOI: 10.1194/jlr.m600296-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel uronic acid-containing acidic glycosphingolipid from the ascidian Halocynthia roretzi

Abstract: A novel uronic acid-containing glycosphingolipid (UGL-1) was isolated from the ascidian Halocynthia roretzi. UGL-1 was prepared from chloroform-methanol extracts and purified by the use of successive column chromatography on DEAE-Sephadex, Florisil, and Iatrobeads. Chemical structural analysis was performed using methylation analysis, gas chromatography, gas chromatography-mass spectrometry, matrix-assisted laser-desorption/ionization time-of-flight mass spectrometry, and 1 H-NMR spectra. The chemical structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Our immunostaining results, sugar composition analysis, and methylation studies confirmed the sugar chain structure of H. aurantium UGL-1 to be identical to that of H. roretzi UGL-1 20 . Given that rhamnose is a 6-deoxymannose, protons H1/H2 of rhamnose are in the gauche conformation, despite an anomeric configuration, showing small 1-3-Hz coupling constants.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Our immunostaining results, sugar composition analysis, and methylation studies confirmed the sugar chain structure of H. aurantium UGL-1 to be identical to that of H. roretzi UGL-1 20 . Given that rhamnose is a 6-deoxymannose, protons H1/H2 of rhamnose are in the gauche conformation, despite an anomeric configuration, showing small 1-3-Hz coupling constants.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, we conclude that the sugar chain structure of UGL-2 is Rha1-3GlcNAc1-3Gal1-4 Fuc1-3 GlcA. In our previous analysis on UGL-1 in the related ascidian species H. roretzi 20 , signals for GlcAβ and Galβ were determined from 2D-NMR data obtained from its structural analog, salcaceramide Galβ1-4 Fucα1-3 Glcβ1-Cer , from the ascidian Microcosmus sulcatus 32 . As a result, a signal at the high-field side was determined as GlcAβ and a signal at the downfield side was determined as Galβ in H. roretzi UGL-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations